Chemical Investigation of Uvaria narum leaves - Bindu, T.K.; Mohamed Shafi, P. (Asian Journal of Chemistry, 2010)
Chemical investigation on the leaves of Uvaria narum hasresulted in the isolation and identification of nonacosane,hentriacontane, tritriacontane, octacosanol, triacontanol, dotriacontanol,tetratriacontanol and β-sitosterol.